Dynamic omniphobic surfaces enable the stable dropwise condensation of completely wetting refrigerants - Kazi Fazle Rabbi; Siavash Khodakarami; Jin Yao Ho; Muhammad Jahidul Hoque; Nenad Miljkovic (Nature Communications)
Abstract Condensation is a vital process integral to numerous industrial applications. Enhancing condensation efficiency through dropwise condensation on hydrophobic surfaces is well-documented. However, no surfaces have been able to repel liquids with extremely low surface tension, such as fluorinated solvents, during condensation, as they nucleate and completely wet even the most hydrophobic interfaces. Here, we introduce a surface functionalization methodology that enables dropwise condensation of fluorinated refrigerants. This approach, compatible with various substrates, combines low contact angle hysteresis Parylene-C with low surface energy silane (P-HFDS) using a highly scalable atmospheric vapor phase deposition technique. Our experimental results demonstrate that the omniphobic P-HFDS coating facilitates dropwise condensation of both natural refrigerants (water, ethanol, hexane, pentane) and synthetic low-global-warming-potential refrigerants (HCFO R1233zd(E) and HFO R1336mzz(Z)) with surface tension as low as 14.6 mN m−1 at 25°C. The P-HFDS coating improves condensation heat transfer coefficients by 274%, 347%, 636%, and 688% for ethanol, hexane, pentane, and R1233zd(E), respectively, compared to filmwise condensation on uncoated metal surfaces. Additionally, the coating demonstrates long-term durability, sustaining steady dropwise condensation for 170 days without apparent degradation. This work pioneers stable dropwise condensation of multiple refrigerants on a structure-less surface, offering a durable, substrate-independent, and scalable solution for low surface energy coatings.